Cotranslational assembly of protein complexes in eukaryotes revealed by ribosome profiling - Shiber, Ayala; Döring, Kristina; Friedrich, Ulrike A.; Klann, Kevin; Merker, Dorina; Zedan, Mostafa; Tippmann, Frank; Kramer, Günter; Bukau, Bernd (Nature, 2018)
Cotranslational assembly is a prevalent mechanism for the formation of oligomeric complexes in Saccharomyces cerevisiae, with one subunit serving as scaffold for the translation of partner subunits.